Penguatan Keterampilan Proyek Sains Siswa Melalui Praktikum Pembuatan Tape Singkong Berbasis Kearifan Lokal Di Sekolah - Lalu Muhammad Rispan Sugi Saputra; Nurul Hidayah (Indonesian Journal of Education and Community Services, 2025)
This study aims to evaluate the effectiveness of cassava tape making practicum in improving students' understanding of the fermentation process as well as practical skills related to biotechnology. This practicum activity was carried out at SMPN Satu Atap 1 Jerowaru involving 24 grade VII students. Data collection was carried out using a questionnaire that measured students' responses to practicum activities. The results of the study showed that the majority of students felt happy and enthusiastic about participating in this practicum, with 91.7% of students feeling happy and 87.5% of students admitting to understanding more about fermentation materials after participating in the practicum. Most students are also interested in trying to make their own tapes at home. However, some students have technical difficulties in sprinkling the yeast evenly and steaming the cassava. Based on these results, it can be concluded that the cassava tape making practicum has succeeded in improving students' understanding of fermentation and providing a fun and applicable learning experience. Increased technical instruction is needed to address the difficulties students face.